Penataan Perpustakaan Sekolah untuk Meningkatkan Minat Literasi Siswa - Agustinus Renaldus Afoan Elu; Maria Crisanti Dhema; Yeni Gradina Kehi; Januarius Gerardus Adal; Maria Inosensia Moi Bai; Freinademetz Abon Galus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The MBKM (Free Learning Independent Campus) activity is an activity that is required for every student at the Faculty of Teacher Training and Education, Widya Mandira Catholic University, Kupang, to disseminate new knowledge and gain factual experiences from the place where field activities are carried out, in order to improve the teacher competency of prospective students. Teacher. This library arrangement activity aims to create a library environment that supports the learning process and to make it easier for students to find reading books that suit their interests. This activity uses a participation method that involves the active participation of MBKM participants outside the classroom and library staff. Results of activities MB KM participants succeeded in completing the library arrangement program well. libraries that were not initially organized, such as books that were still scattered on tables and not arranged according to book categories, were then arranged on bookshelves according to book categories. with library arrangement activities students will be more interested in visiting and even reading books in the library.